Imagined states : law and literature in Nigeria, 1900-1966 - Baxter, Katherine Isobel, 1976- (Edinburgh critical studies in law, literature and the humanities., 2019)
Examines representations of the law in colonial and postcolonial fiction from and about Nigeria Imagined States examines representations of the law in British and Nigerian high-brow, middle-brow and popular fiction and journalism. Drawing on a rich range of examples, the book focuses on the imaginative role that the state of exception played in the application of indirect rule during British colonialism and in the legal machinations of the postcolonial state. It reads works by Chinua Achebe, Joyce Cary, Cyprian Ekwensi and Edgar Wallace, together with a range of Nigerian market literature and journalism.